PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELASIV SDN 009BATURIJAL HILIR KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Angga Lukmana; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This research at performs since its low usufruct IPS'S studying student brazes IV. SDN 009 BaturijalDownstreams that haven't reached KKM (Minimum thoroughness criterion) one that is established which is 65. This appears from peneletian's startup data of 20 students which reach points according to KKM as much 8 students with averagely brazes 57,75. Its low is yielding studies it at causes since teacher be still dominate deep learning so student involvement in learning becomes less active. Base about problem research do that action brazes with learnings model implement get Problem basis. This research intent to increase IPS'S studying result student brazes IV. SDN 009 Baturijal School Year Downstream 2014 / 2015. This research is executed deep two cycles, whereabouts on each cycle it consisting of two-time appointment gazes to show face and once daily dry run. With be applied Model Learning gets Problem basis, therefore gets to increase IPS'S studying result student brazes IV. SDN 009 BaturijalDownstreams on social problem material. It can at see of thoroughness result studies individual and klasikal which gotten by student on base score which is with thoroughness percentage 40%, with average 57,75, worked up on i. cycle with thoroughness percentage 65% by average 68. Worked up again on cycle II.which is with thoroughness percentage 90% by average 76,75. On Activity learns first cycle with percentage average 72,9% worked up as 87,5% on second cycle. Student activity on first cycle with percentage average 73,21% worked up as 87,5% on second cycle. Of acquired data as above as gets to be known that pass through learning model Implement gets Problem basis, can increase IPS'S studying result student brazes IV. SDN 009 BaturijalDownstreams.Key word: PBM, IPS'S Learned result